Flipped Classroom Media Sebagai Upaya Peningkatan Kemampuan Bahasa Inggris APMD Yogyakarta - Sunardi, Andhina Ika; Palupi, Risqi Ekanti Ayuningtyas (Universitas Muhammadiyah Ponorogo, 2024)
The research entitled Implementation of Flipped Classroom in English learning at APMD Yogyakarta aims to help students understand English courses in the first semester of students. Flipped Classroom is one of the teaching methods where students get learning materials along with exercises and assignments (individual or group) in the form of videos and access them online through Google Classroom, to be done outside the classroom to be discussed during course hours. So, during class, what the teacher does is to review the material, discuss assignments or exercises, and answer questions from students who still don't understand the material given. Meanwhile, students who come to class are expected to have gained an understanding of the material presented. This method is tried to be applied to overcome the time constraints given for this course, which is only 1x a week for 2 hours of lectures (@ 45 minutes). It is hoped that by implementing this method, student will enhance their English skill and can easily understand the material presented marked by increasing studentsâ€™ score.Â